ECONOMICS OF RAISING JERSEY X ASSAM LOCAL CROSSBRED CALVES AT DIFFERENT LEVELS OF PROTEIN IN CALF STARTER - N.K. Sarma; K. Zothanpuii; T.K. Amonge (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Aim of the present investigation was to evaluate the economics of raising Jersey X Assam local crossbred calves reared under three different calf starters containing three different DCP levels. Twelve  new born crossbred calves of either sex were randomly divided into three groups and reared under three different calf starters containing three different DCP levels of 20  (group I), 22 (group II) and 24 (group III) per cent with 75-76 per cent TDN. The experimental calves were offered whole milk, green fodder and calf starter as per standard feeding schedule (ICAR, 1991). The calves of group I showed significantly (P